Human rights and world trade : hunger in international society - Gonzalez-Pelaez, Ana, 1974- (London ; New York : Routledge, 2005)
"This book provides an analysis of the political viability of human rights and offers an in-depth investigation of the largest violation of human rights: world hunger." "Demonstrating the interaction between international relations and international political economy, this book will be of significant interest to IR theorists as well as human rights scholars and practitioners concerned with basic rights and the problem of hunger."--Jacket
Introduction -- The problem of hunger -- Basic rights : political origins -- Basic rights in international society : the right to food -- International trade and the options for eradicating hunger -- Can international society eliminate hunger? -- Conclusion : assessment of Vincent's basic rights project.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Vincent, R. J., -- 1943-; Vincent, R. J., -- 1943-; Food supply; Hunger; Human rights; International trade -- Social aspects; International economic relations; Hunger; Human Rights; Food Supply; Faim; Droits de l'homme (Droit international); Commerce international -- Aspect social; Aliments -- Approvisionnement; SOCIAL SCIENCE -- General; BUSINESS & ECONOMICS -- Infrastructure; Food supply; Human rights; Hunger; International economic relations; International trade -- Social aspects; Ernährungssicherung; Welthandel; Hunger; Recht op voedsel; Internationale handel; Honger; Internationaal recht